(untitled) (Acta Scientiarum. Biological Sciences, 2017)
Germination of diaspores and the seedling structure of Ruprechtia laxiflora Meissn. (Polygonaceae) which is a secondary species frequent in forest remnants are described. Seedlings were embedded in hydroxymethacrylate and sectioned in a rotary microtome according to usual techniques in plant anatomy. For bioassays of germination, the experimental design was completely randomized in a 3x2 bifactorial arrangement, corresponding to three temperatures (20, 25 and 30°C) and two light conditions (photoperiod and continuous darkness) for the diaspores newly harvested and in a 4x2 bifactorial arrangement, corresponding to four temperatures (15, 20, 25 and 30°C) and two light conditions (photoperiod and continuous darkness) for diaspores analyzed after storage. There was no interaction between the factors light condition and temperature for germination parameters analyzed. However, the temperature affected the germination and diaspores maintained at 25°C showed a shorter mean time and higher germination speed index. Seedlings are phanerocotylar and epigeal with tetrarch root, intermediate-low type of root-stem transition and trilacunar cotyledonary node.